2012
DOI: 10.1111/j.1469-8137.2012.04194.x
|View full text |Cite
|
Sign up to set email alerts
|

TaCKX6‐D1, the ortholog of rice OsCKX2, is associated with grain weight in hexaploid wheat

Abstract: Summary• The cytokinin oxidase ⁄ dehydrogenase (CKX) gene plays a principal role in controlling cytokinin levels and has been shown to be a major quantitative trait locus (QTL) affecting grain number in rice. However, the function and evaluation of the haplotypes of the wheat CKX gene have yet to be illustrated.• In this study, TaCKX6-D1, a wheat ortholog of rice OsCKX2, was cloned and its haplotype variants were determined to be significantly associated with the 1000-grain weight on the basis of linkage mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(169 citation statements)
references
References 59 publications
6
161
2
Order By: Relevance
“…In agreement with Michael and Seiler-Kelbitsch [8], Zhang et al [9] observed a relationship whereby CK accumulation corresponded with increased kernel mass in wheat. A study by Ashikari et al [5] indicated that there was a positive relationship between the number of grains per panicle, branching and CK content in rice.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In agreement with Michael and Seiler-Kelbitsch [8], Zhang et al [9] observed a relationship whereby CK accumulation corresponded with increased kernel mass in wheat. A study by Ashikari et al [5] indicated that there was a positive relationship between the number of grains per panicle, branching and CK content in rice.…”
Section: Introductionmentioning
confidence: 59%
“…The highest yielding cultivar, GB046034, which had the greatest number of kernels per spike, and the greatest total mass of kernels per spike, also had the highest levels of both total CKs and tZ at both the fourth stage and the critical fifth stage of kernel development. Previous studies on barley [8] and wheat [9] suggest that the cultivar producing larger grains should exhibit higher levels of CKs. Gene silencing of HvCKX1 in barley also resulted in higher mass seeds [14].…”
Section: Ck Profilesmentioning
confidence: 99%
“…The locus Grain number 1 (Gn1) in rice encodes CYTOKININ OXIDASE2 (CKX2), which breaks down cytokinin and limits the number of spikelets and panicle branches (Ashikari et al 2005), as does its ortholog in wheat (Zhang et al 2012). Conversely the cytokinin biosynthetic protein LONELY GUY (LOG) increases the number of branches (Sakakibara 2006).…”
Section: Numbers Of Branches or Spikelets At Each Order Of Branchingmentioning
confidence: 99%
“…The reduced expression of Gn1a causes cytokinin accumulation in inflorescence meristem and increases the number of spikelets, thus enhancing GY , Table 11.2). Zhang et al (2012) reported, TaCKX6-D1 gene, a wheat ortholog of rice OsCKX2 gene which was cloned and its haplotype variants were determined to be significantly associated with 1,000-grain weight on the basis of linkage mapping association and gene expression analysis. A major QTL for flag leaf length, qFLL6.2 on chromosome 6 has been identified from Indica rice cross Zhenshan 97/Milyang 46 and explained 52.7 % of PV.…”
Section: Grain Yield and Yield Componentsmentioning
confidence: 99%